The Effect Of The Intensity Of Playing Shopee Cocoki Gamification On Customer Engagement And Customer Loyalty On Users Shopee Application In Indonesia - Amelia Putri; Dora Rinova (Cita konsultindo, 2024)
This study aims to determine the effect of the intensity of playing Shopee Cocoki gamification on customer engagement and customer loyalty in the Shopee application in Indonesia. Applying quantitative research techniques with non-probability sampling method purposive sampling approach. The research population is users of the Shopee In-App Games feature in Indonesia with a sample size of 100 respondents based on sample criteria. In this study, data processing was carried out using SmartPLS 3. Through this research, the results were obtained in the form of: 1) the intensity of playing Shopee Cocoki gamification has a positive and significant effect on customer engagement in the Shopee application in Indonesia; 2) the intensity of playing Shopee Cocoki gamification has a positive and significant effect on customer loyalty in the Shopee application in Indonesia.